2018
DOI: 10.14569/ijacsa.2018.090551
|View full text |Cite
|
Sign up to set email alerts
|

Technical and Perceived Usability Issues in Arabic Educational Websites

Abstract: Educational websites are often used as effective communication mediums to provide useful information for students and course instructors. The current study explores the perceived usability of three top-ranked Arabic educational websites across seven key usability components: effectiveness, efficiency, learnability, memorability, errors, satisfaction, and content. Moreover, the study also identifies the key technical and usability issues that currently exist within Arabic educational websites. A two-phase proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
7
0
1
Order By: Relevance
“…As such, many previous studies have argued that the design of mobile UI needs to be engaging, meaningful, usable, easy to use and motivating (Kascak, Rébola, & Sanford, 2014), particularly for elderly users (Chadwick-Dias, McNulty, & Tullis, 2003;Franklin & Myneni, 2018). Studies on the relationship amongst UI components usability and Arabic culture are still in their early stages (Benaida, 2014). This study has attempted to show how usability is influenced by Arab culture and how UI design based-culture can be devised to help elderly Arab users use the interactive mHealth app UI efficiently.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As such, many previous studies have argued that the design of mobile UI needs to be engaging, meaningful, usable, easy to use and motivating (Kascak, Rébola, & Sanford, 2014), particularly for elderly users (Chadwick-Dias, McNulty, & Tullis, 2003;Franklin & Myneni, 2018). Studies on the relationship amongst UI components usability and Arabic culture are still in their early stages (Benaida, 2014). This study has attempted to show how usability is influenced by Arab culture and how UI design based-culture can be devised to help elderly Arab users use the interactive mHealth app UI efficiently.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some studies examined the performance of Arabic websites by inspecting the internal attributes of the HTML pages. For example, [25] compared three Arabic educational websites and reported technical issues related to the site loading speed as a direct consequence of the excessive number of HTML objects and images and their large size. Similarly, [26] inspected the number of HTML files, objects, images, CSS files, broken links and size of images on 9 websites using two specialized online tools.…”
Section: F the Research Gapmentioning
confidence: 99%
“…fewer HTTP requests, compressed files…etc.). Author in [25] suggested that the site should take less than 3 seconds to load fully otherwise users might leave the site.…”
Section: The Performance Of the Arabic Websitesmentioning
confidence: 99%
“…In this study, the author explores usability problems in the Arab North African educational websites, the satisfaction of Arabic users is still so far. The websites failed to satisfy all usability variables including slow loading speed and high number of HTML objects [24]. In addition, the level of usability in a non-Arabic country was investigated [3], [40] in Turkish universities, the users found the university websites easy to use and that the websites proved to be a very useful source of information regarding the university.…”
Section: Literature Reviewmentioning
confidence: 99%